Factors Influencing Neoadjuvant Chemotherapy Response in Breast Cancer - BILQUEES SULEMAN, QASIM AHMED, RAJIA LIAQAT, ASIMA NAZ, TOOBA FATEEN, (Journal of Fatima Jinnah Medical University, 2018)
Background: Breast cancer is a major public health issue globally leading to more than a million deaths annually worldwide. For carcinoma of breast, factors as age of the patient, menopausal status, tumor size, tumor type, tumor grade, estrogen receptor status (ER), progesterone receptor status (PR) and HER2neu expression are important prognostic indicators. Objective: Objective of this study was to observe the response of neoadjuvant chemotherapy on breast tumor and lymph nodes and to identify the clinical and pathological factors. Patients and Methods: This was a descriptive case series conducted in Pathology department, Shaukat Khanum Memorial Cancer Hospital and Research Center Lahore for eight months. Total 55 patients with biopsy proven breast cancer were taken. Data regarding tumor size, tumor type, tumor grade, hormone receptor status (ER status, PR status) and others including age of the patient, menstrual status and HER2neu status was collected on proforma. Lumpectomy and mastectomy specimens of these patients after they have received neoadjuvant chemotherapy were taken. Data were entered and analyzed on SPSS version 10. Results: There were 41 (74.5%) premenopausal and 14 (25.5%) postmenopausal women in our study. Invasive ductal carcinoma was the primary breast tumor in 50 (90.9%) patients while invasive lobular carcinoma was in 5 (9.1%) patients. HER-2/neu showed positivity i-e positive 2+ in 11(20%) cases and positive 3+ in 22(40%) cases. HER 2-neu showed negativity i-e negative 12(21.8%) cases and negative1+ in 10(18.2%) cases. Grade IV (Complete pathological response) was achieved in 12 patients, Grade III (50-99% response) was achieved in 19 patients, Grade II(<50% response) was achieved in 12 patients and Grade I (No response) was seen in 12 patients. Complete pathological response in lymph nodes was achieved in 8(14.5%) cases, partial response in 19(34.5%) and no response in 18(32.7%) cases. There was no evidence of metastasis in 10(18.2%) cases.